PHP, MySQL, JavaScript & HTML5 all-in-one for dummies - Suehring, Steve; Valade, Janet (For dummies, 2013)
Get the basics on four key web programming tools in one great book! PHP, JavaScript, and HTML5 are essential programming languages for creating dynamic websites that work with the MySQL database. PHP and MySQL provide a robust, easy-to-learn, open-source solution for creating superb e-commerce sites and content management. JavaScript and HTML5 add support for the most current multimedia effects. This one-stop guide gives you what you need to know about all four! Seven self-contained minibooks cover web technologies, HTML5 and CSS3, PHP programming, MySQL databases, JavaScript, PHP with templates, and web applications. Addresses how PHP, MySQL, JavaScript, and HTML5 are vital tools for creating dynamic, database-driven websites and are especially important for e-commerce sites Serves as essential reading for web designers who are new to these technologies, offering a crash course covering all of these powerful technologies in this handy volume of seven self-contained minibooks Covers how to program in PHP and how to create and administer a MySQL database as well as how to manipulate MySQL data via a web interface Shows how to create a secure website and how to code popular e-business applications such as login programs and shopping carts With seven books in one, PHP, MySQL, JavaScript & HTML5 All-in-One For Dummies will turn your website into the center of attention in no time at all.